The Influence of Anthropometric Characteristics on Punch Impact - Manuel Pinto; João Crisóstomo; Gil Silva; Luís Monteiro (Sports)
Objective: This review examined the influence of anthropometric characteristics, such as body height (BH) and body mass (BM), on the impact of punches in striking-combat sports. Despite their perceived importance for combat strategy, the relationship between these characteristics and punch impact remains unclear. Methods: We included experimental, quasi-experimental and cross-sectional studies. The search was conducted on 30 August 2024, in three databases. The review analyzed 23 studies involving 381 participants (304 men, 30 women, 47 participants of unknown gender). Various instruments were used in the included studies, including ten instruments used to measure impact force and two instruments used to measure impact power. Results: Impact force ranged from 989 ± 116.76 to 5008.6 ± 76.3 N, with rear-hand straight punches and rear-hand hooks producing the greatest force. The PowerKube, a device specifically designed to measure punch impact power, revealed that the rear-hand straight punch generated the highest power, ranging from 15,183.27 ± 4368.90 to 22,014 ± 1336 W. While higher BM categories were associated with stronger punches, BM alone was not the only predictor. Other factors, such as technique, gender, and sport type, also played roles. The relationship between BH and punch impact showed mixed results. Conclusions: The data suggest that while higher BM categories are associated with greater punch impact, BM is not the only determining factor. The relationship between BH and impact also showed mixed results, with no clear association found. The review highlights the lack of a “gold standard” instrument for evaluating punch impact.